Influence of the porosity caused by incomplete sintering on the mechanical behaviour of lanthanum silicate oxyapatite - Moreira Toja, Ramiro Julián (2018)
Lanthanum silicate oxyapatite (LSO) is an encouraging material for its use as an electrolyte in intermediate temperature solid oxide fuel cells. There is a vacancy in knowledge respecting to LSO's mechanical properties, and thus they are the scope of research of the present work. Isostatically pressed bars were sintered at temperatures from 1200 °C to 1500 °C. The dependence of Young's modulus with porosity was fitted using three different modeling curves, and extrapolated for a fully dense material. The fitting of these equations give an E0 between 144 GPa and 169 GPa. This is the first time that LSO's Young's modulus is reported. Flexural strength,Vickers hardness, fracture toughness (KIC) from microindentation cracks and nanohardness were also measured. Scanning electron micrography was performed on both a sub-sintered and the most sintered sample, and the microstructure and fracture mechanism were analyzed. In general, the mechanical behaviour is similar to other intermediate temperature solid oxide electrolytes. The fracture mechanism of the most sintered sample makes it well-suited for future SOFC applications.